Implementation Of Articles 98 And 99 Of Law Number 32 Of 2009 On Environmental Protection And Management Against Deforestation Perpetrators - Sudiantari, Kadek Yuni; Dantes, Komang Febrinayanti; Hadi, I Gusti Ayu Apsari (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Deforestation is one of the forms of environmental damage that has a significant impact on ecosystem balance and the sustainability of natural resources. Therefore, strict legal regulations are required to address any actions that cause environmental damage. This study aims to analyze the regulation of environmental crimes in Law Number 32 of 2009 concerning Environmental Protection and Management, examine the criminal liability of deforestation perpetrators based on Articles 98 and 99, and identify the implementation and challenges in its law enforcement. This research uses a normative legal research method with a statutory approach and a conceptual approach. The legal materials used include legislation, legal literature, and relevant scientific journals. The results of the study show that Law Number 32 of 2009 has provided a clear legal basis for law enforcement against actions that cause environmental pollution and environmental damage. Criminal liability for deforestation perpetrators can be imposed when the act is committed intentionally or due to negligence, and it can be applied not only to individuals but also to corporations. However, law enforcement against deforestation perpetrators still faces several challenges, such as difficulties in the process of proof, the complexity of corporate structures, and limited supervision. Therefore, strengthening environmental law enforcement in a more effective manner is necessary.